2004
DOI: 10.1074/jbc.m404722200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Zinc Finger Structure in the Large Subunit of Human General Transcription Factor TFIIE

Abstract: The zinc finger domain in the large subunit of TFIIE (TFIIE␣) is phylogenetically conserved and is essential for transcription. Here, we determined the solution structure of this domain by using NMR. It consisted of one ␣-helix and five ␤-strands, showing novel features distinct from previously determined zinc-binding structures. We created point mutants of TFIIE␣ in this domain and examined their binding abilities to other general transcription factors as well as their transcription activities. Four Zn 2؉ -li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…TFIIEβ WH2 residues 150–207 were aligned with Sulfolobus tokodaii STO12A residues 25–106 (PDB: 2D1H) 73 . The human ZR domain, residues 125–164 (PDB: 1VD4) 74 , was docked near the base of the stalk domain of Pol II. The human TFIIEβ WH1 residues 75–146 (PDB: 1D8J) 75 were fitted into the region proximal to TFIIF RAP30 WH domain.…”
Section: Methodsmentioning
confidence: 99%
“…TFIIEβ WH2 residues 150–207 were aligned with Sulfolobus tokodaii STO12A residues 25–106 (PDB: 2D1H) 73 . The human ZR domain, residues 125–164 (PDB: 1VD4) 74 , was docked near the base of the stalk domain of Pol II. The human TFIIEβ WH1 residues 75–146 (PDB: 1D8J) 75 were fitted into the region proximal to TFIIF RAP30 WH domain.…”
Section: Methodsmentioning
confidence: 99%
“…The TFIIE small subunit Tfa2 contains two tandem winged helix domains (39,40). NMR structures of three conserved TFIIE domains have been determined (39,41,42), but only a low resolution EM structure of the TFIIE heterodimer is available (43). This is likely due to difficulties in obtaining diffraction quality crystals of the complete complex.…”
Section: Fig 3 Identification Of Bdrg Derived Monolinks (A) and Loomentioning
confidence: 99%
“…The structure of the archaeal homologue of the N-terminal part of TFIIEα, TFE, revealed an extended WH domain that had extra helices on the N and C termini, and indicated that the domain does not interact with DNA 133 . The essential zinc-finger domain from human TFIIEα has a novel topology 134 . The C-terminal acidic region forms a compact domain 135 that is required for strong interaction with TFIIH 131 , apparently through binding of the pleckstrin homology domain of p62 in TFIIH 135 .…”
Section: Rpb4-rpb7mentioning
confidence: 99%